Dispersion Engineered Silicon Nanocrystal Slot Waveguides for Soliton Ultrafast Optical Processing. (15th August 2011) - De Leonardis, Francesco; Passaro, Vittorio M. N.
Abstract : We propose, for the first time to our knowledge, the theoretical investigation of silicon nanocrystals-based sandwiched slot waveguides which are dispersion-engineered for exciting optical solitons inside very short structures (only 1.2 mm long). Several parametric simulations have been performed by means of finite element method in order to individuate the best waveguide cross-sections for achieving an anomalous dispersion regime around 1550 nm.